Model E-Satisfaction Pengguna Layanan Mobile Banking selama Pandemi Covid-19 (Survey pada Nasabah Bank Nagari) - Nurul Afifah Usman; Eri Besra; Syafrizal Syafrizal (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2022)
Mobile banking had a significant increase during the Covid-19, therefore Bank Nagari had to improve its performance by maintaining e-satisfaction This study tests the e-satisfaction model for mobile banking Bank Nagari services users during Covid-19, which is influenced by mobile banking service quality and online relationship quality. Data were analyzed using AMOS's 26 version structural equation model (SEM) as the software used and the type of this study is quantitative explanatory. The sampling technique uses quota sampling with a sample number of 120 respondents who used mobile banking during the Covid-19. The results showed that mobile banking service quality and online relationship quality positively and significantly affected e-satisfaction. This model can be used for Bank Nagari as strategic management to improve customer satisfaction in mobile banking by improving mobile banking service quality and online relationship quality.  This study extends the literature related to the e-satisfaction model in using mobile banking services, especially for customers of Bank Nagari.